2014
DOI: 10.1063/1.4883892
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of nanoporous three-dimensional graphene networks

Abstract: We propose three dimensional-graphene nanonetworks (3D-GN) with pores in the range of 10 ∼ 20 nm as a potential candidate for thermoelectric materials. The 3D-GN has a low thermal conductivity of 0.90 W/mK @773 K and a maximum electrical conductivity of 6660 S/m @ 773 K. Our results suggest a straightforward way to individually control two interdependent parameters, σ and κ, in the nanoporous graphene structures to ultimately improve the figure of merit value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Here, we investigate a 2D-2D junction, the graphenegraphene junction, which is common in graphene foams that are promising for thermal management and energy storage [53][54][55][56][57] . As indicated in Fig.…”
Section: Phonon Local Non-equilibrium In Graphene-graphene 2d Junctionmentioning
confidence: 99%
“…Here, we investigate a 2D-2D junction, the graphenegraphene junction, which is common in graphene foams that are promising for thermal management and energy storage [53][54][55][56][57] . As indicated in Fig.…”
Section: Phonon Local Non-equilibrium In Graphene-graphene 2d Junctionmentioning
confidence: 99%
“…Optimum Zn 0.95 Ni 0.05 O/PPP nanocomposites containing 5 wt % PPP exhibited an increase of electrical conductivity by ∼45% at 650 K and a reduction of thermal conductivity by ∼30% at 1173 K. On the other hand, graphene, a two-dimensional (2D) flat monolayer of sp 2 -bonded carbon atoms, has recently attracted tremendous attention owing to its superior merits of large specific surface area and good electrical conductivity . These favorable characteristics make graphenes potentially excellent TE materials. Therefore, it can be envisioned that integration of graphene into inorganic TE materials would enhance their TE performance. One such example was recently reported by Dong et al that the in situ chemistry method was used for PbTe–graphene nanocomposites for TE applications .…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Moreover, it also indicates the crystallinity of the samples did not significantly alter. [ 34 ] It is observed that the peak position of D‐band (≈1340 cm −1 ), G‐band (≈ 1580 cm −1 ), and 2D‐band (2685 cm −1 ) did not show an obvious shift, which implies that addition of CNT or CB did not cause the softening or hardening of phonons. [ 35 ] The lower I D / I G ratio of our samples as compared to reported data for FLGs [ 27 ] and the least defects as indicated by very low peak intensity of D‐band demonstrate the high quality of the prepared material and fewer layers of the prepared FLG.…”
Section: Resultsmentioning
confidence: 99%
“…In-plane [40] Suspended single layered graphene (SLG) ≈4840-5300 RT - [41] Suspended graphene ≈3000-5300 RT In-plane [42] Pyrolytic graphite ≈2000 RT In-plane -Pure pitch-bonded graphite ≈200 RT In-plane [43] FLG (n = 2-4) ≈2800-1300 RT In-plane [44] SLG 600 RT - [45] Suspended graphene ≈2600-3100 350 In-plane [43] Porous 3D-graphene networks 0.54-0.90 298-773 - [34] Graphene nanoribbon(n < 5) ≈1000-1400 RT - [46] Oxygen plasma treated defected graphene supported on substrate 36 -- [47] Graphene pellet 0.38-3.02 303-363 Parallel to the pressing direction [48] MWCNT pellet 1.60-2.25 300-923 Parallel to the pressing direction [49] Carbon black pellet ≈0.2-0. pellet which is predictably lower than the graphene sheets.…”
Section: Resultsmentioning
confidence: 99%